Prevalence of sicca syndrome in the Peruvian population - Moreno-Quispe L.A. (2019)
Objectives: Sjögren's syndrome is a complex and heterogeneous autoimmune disease characterised by ocular and oral dryness (1), which mainly affects the exocrine glands. The objective of this study was to determine the prevalence of sicca syndrome (SS) in the Peruvian population. The age and gender of patients with SS and their national prevalence and in each of the departments were defined. Methods: This was a cross-sectional prevalence study. All the people for whom the Ministry of Health (MINSA) in Peru covered health treatments from January to December 2016 were taken into account. The patients with SS were either newly or previously diagnosed with sicca syndrome (Sjögren's) according to the international classification of diseases version 10 (ICD-10) of the World Health Organization (WHO). The prevalence was determined considering the number of cases of SS in the total population registered by the Ministry of Health (MINSA). Results: 1,301 cases of SS were observed in a total population of 15,417,345 people served in 25 territories. The prevalence of SS in this population was 0.0084%, the prevalence rate was 8.4 cases per 100,000 persons (95% CI: 7.99-8.91). The prevalence of SS was higher in the territories of Tacna, Lima, La Libertad, Arequipa, Callao, and Apurímac. Conclusions: The results of this study show the prevalence of SS in the Peruvian population and serve to strengthen the health strategies of rheumatology, ophthalmology, and oral health to improve the diagnosis, treatment, follow-up of the disease, and the quality of life of patients with SS.